2019
DOI: 10.2147/dmso.s209938
|View full text |Cite
|
Sign up to set email alerts
|

<p>Characterization of variable presentations of diabetic ketoacidosis based on blood ketone levels and major society diagnostic criteria: a new view point on the assessment of diabetic ketoacidosis</p>

Abstract: Aim We aimed to evaluate the clinical utility of blood ketone measurement and to test the performance of the diagnostic criteria for diabetic ketoacidosis (DKA) issued by the American Diabetes Association, the Joint British Diabetes Societies, and the American Association of Clinical Endocrinologists and the American College of Endocrinology. Methods This retrospective analysis included 278 patients with suspected DKA who were hospitalized at 4 university hospitals and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…It is mainly characterized by hyperglycemia, hyperkalemia, dehydration, electrolyte imbalance, and acidosis. Diabetic ketoacidosis can induce tissue ischemic injury as the disease progresses, and the mortality rate is high [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is mainly characterized by hyperglycemia, hyperkalemia, dehydration, electrolyte imbalance, and acidosis. Diabetic ketoacidosis can induce tissue ischemic injury as the disease progresses, and the mortality rate is high [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al reported significantly decreased biochemical levels at the time of death vs. at the time of admission. SBP, DBP, creatinine level, and serum lactate level were found to be predictors of mortality [ 22 ]. In our study, significantly different HR and RR were observed in patients with severe DKA (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies imply that the effects of DKA on long-term prognosis are not only possibly due to ethnical differences but also different physiological conditions at the time of initial T1DM diagnosis. In fact, a recent report suggested that the co-occurrence of various medical conditions with DKA, such as lactic acidosis, also result in worse clinical outcomes [ 21 ]. Although we speculated in this study that high HbA1c levels might suggest deleterious metabolic conditions to the residual islet cell function, their exact effects were not evaluated, especially in various ethnicities.…”
Section: Discussionmentioning
confidence: 99%